2010
DOI: 10.1016/j.jprot.2009.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Proteins secreted by embryonic stem cells activate cardiomyocytes through ligand binding pathways

Abstract: Human embryonic stem cells (hESC) underly embryogenesis but paracrine signals associated with the process are unknown. This study was designed to 1) profile native proteins secreted by undifferentiated hESC and 2) determine their biological effects on primary neonatal cardiomyocytes. We utilized multi-analyte, immunochemical assays to characterize media conditioned by undifferentiated hESC versus unconditioned media. Expression profiling was performed on cardiomyocytes subjected to these different media condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Although no definite exocytotic events were observed, electron micrographs suggest a goblet-cell-like secretion mechanism (Fig. 7C), which is supported by previous results showing the secretion of cytosolic and cytoskeletal proteins in the proteome of hESC-conditioned medium (LaFramboise et al, 2010). By contrast, evidence of autophagy was uncommon, but both lines contained large multivesicular bodies signifying heterophagy.…”
Section: The Higher Atp Turnover In Hescs Compared With Nscs At Slowesupporting
confidence: 86%
See 1 more Smart Citation
“…Although no definite exocytotic events were observed, electron micrographs suggest a goblet-cell-like secretion mechanism (Fig. 7C), which is supported by previous results showing the secretion of cytosolic and cytoskeletal proteins in the proteome of hESC-conditioned medium (LaFramboise et al, 2010). By contrast, evidence of autophagy was uncommon, but both lines contained large multivesicular bodies signifying heterophagy.…”
Section: The Higher Atp Turnover In Hescs Compared With Nscs At Slowesupporting
confidence: 86%
“…As the total energy budget was greater in hESCs than in NSCs, this indicated a faster macromolecule synthesis rate in hESCs; however, in the absence of increased cell division, these extra macromolecules must ultimately be degraded or secreted. hESCs have been shown to secrete a diverse range of chemokines, cytokines, growth factors and matrix remodelling enzymes, along with cytosolic and cytoskeletal components (Bendall et al, 2009;LaFramboise et al, 2010). We found that hESCs had morphological indications of goblet-cell-like secretion and secreted significantly more protein into the extracellular environment than did NSCs.…”
Section: Discussionmentioning
confidence: 78%
“…Some of the factors presented in the ESCM such as MIF, PAI-1, sICAM-1, IL-6 and IL-8 have been detected in conditioned medium from undifferentiated human H1/H9 (Bendall et al 2009) and Hsf1 ES cell lines (LaFramboise et al 2010). Interestingly, undifferentiated human H1 and H9 ES cell lines could produce bFGF and TGFb1 which have been identified as growth factor for MSCs proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells whose paracrine effects have been documented include human peripheral blood-derived epithelial stem cells [21], nucleated bone marrow cells [22], skeletal myoblasts [23] and ESCs [6,9], among others. …”
Section: Discussionmentioning
confidence: 99%
“…Embryonic stem cells (ESCs) are considered to be a more reliable cell source for myocardial regeneration. Besides, recent studies [5,6,7,8,9] found that ESCs could also benefit the heart via a paracrine mechanism. However, the ethical issues associated with embryo manipulation preclude ESCs from clinical application.…”
Section: Introductionmentioning
confidence: 99%